Oxygen sensing; a stunningly elegant molecular machinery highjacked in cancer. (2nd July 2020) - Claesson-Welsh, Lena
Abstract: Oxygen is of fundamental importance for most living organisms, and the maintenance of oxygen homeostasis is a key physiological challenge for all large animals. Oxygen deprivation, hypoxia, is a critical component of many human diseases including cancer, heart disease, stroke, vascular disease, and anaemia. The discovery of oxygen sensing provides fundamental knowledge of a stunningly elegant molecular machinery; it also promises development of new therapeutics for serious diseases such as cancer. As a result of their impressive contributions to our understanding of the mechanisms by which cells sense oxygen and signal in hypoxia, Gregg Semenza, Peter Ratcliffe, and William Kaelin were awarded the Nobel Prize in 2019.